Prediction of stress-corrosion cracking using electrochemical noise measurements: A case study of carbon steels exposed to H2O-CO-CO2 environment. (February 2023) - Merwe, J.W. van der; du Toit, M.; Klenam, D.E.P.; Bodunrin, M.O.
Highlights: Stress-corrosion cracking of carbon steel was estimated in H20-CO-CO2 environment using electrochemical noise measurement. Parameters influencing stress corrosion cracking in the absence of high-resolution crack length detection was estimated using a novel electrochemical nose measurement. Current response measurement was used to forecast the stress intensity threshold for stress corrosion cracking. Abstract: At 45 °C, the stress-corrosion cracking (SCC) threshold was determined using current response measurements when carbon steels were exposed to a 50 %CO-50 %CO2 -H2 O environment. These measurements were performed by introducing an external "crack wall" surface and measuring a fraction of the current flow between the crack tip and this external surface. The current flow was measured between this external surface and the crack tip, by insulating most of the double cantilever beam samples, and using a zero-resistance ammeter (ZRA) to measure the current. These measurements showed that the threshold for cracking determined with this method corresponded well with the KISCC value measured for the same system. Crack tip activity was also measured, but it was difficult to correlate the current response data with the crack propagation rates, because of the crack length measurement resolution. However, it was possible to indicate the increased crack tip activity when the stress intensity showed slight variations, or for threshold stress intensity increase rates. The technique confirms the estimation of stress-corrosion thresholds and can be used to evaluate the influence of parameters on cracking in the absence of high-resolution crack length detection instrumentation.